Upland rice, household food security and commercialization of upland agriculture in Viet Nam - Pandey, S.; Khiem, N. T.; Waibel, H.; Thien, T. C. (IRRI, 2006)
This book provides knowledge of the characteristics of upland systems and recent development trends, a conceptual approach, an analytical approach, a descriptive analysis of farm survey data, an econometric analysis, a normative analysis of cropping choices, and more.